2021
DOI: 10.5613/rzs.51.1.3
|View full text |Cite
|
Sign up to set email alerts
|

"Ženski sport nije pravi sport": negativni stereotipi prema sportašicama i doživljaj rodne neravnopravnosti u rukometu u Hrvatskoj

Abstract: Osnovni cilj istraživanja bio je utvrditi koliko se često mladi rukometaši i rukometašice susreću s negativnim stereotipima prema sportašicama. Osim spomenutoga, ispitali smo razlikuju li se sportašice koje su u različitom stupnju izložene negativnim stereotipima u doživljaju rodne neravnopravnosti koja se očituje u nejednakim uvjetima treniranja i nejednakom načinu vrednovanja sportskih postignuća mladića i djevojaka koji treniraju u njihovom sportskom klubu. U istraživanju je sudjelovalo 522 rukometaša/ica (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[14][15][16][17][18]81 This could be explained by the negative influence of gender roles and stereotypes on sports and exercise participation among girls. 110,111 For example, a recent Croatian study 112 found that around 95.0% of adolescent handball players encountered some form of gender stereotypes related to sports participation (eg, "sport is not for girls" and "female sport is less attractive than male sport"), with girls being significantly more exposed to such stereotypes than boys. Therefore, eliminating factors that lead to gender inequality and discrimination in sports may be needed to increase girls' physical activity.…”
Section: Overall Physical Activity Organized Sport Active Play and Ac...mentioning
confidence: 99%
“…[14][15][16][17][18]81 This could be explained by the negative influence of gender roles and stereotypes on sports and exercise participation among girls. 110,111 For example, a recent Croatian study 112 found that around 95.0% of adolescent handball players encountered some form of gender stereotypes related to sports participation (eg, "sport is not for girls" and "female sport is less attractive than male sport"), with girls being significantly more exposed to such stereotypes than boys. Therefore, eliminating factors that lead to gender inequality and discrimination in sports may be needed to increase girls' physical activity.…”
Section: Overall Physical Activity Organized Sport Active Play and Ac...mentioning
confidence: 99%